Upconversion luminescence enhancement by Fe3+ doping in CeO2:Yb/Er nanomaterials and their application in dye-sensitized solar cells. Issue 32 (19th May 2020) - Bai, Jingyi; Duan, Pingping; Wang, Xin; Han, Gui; Wang, Min; Diao, Guowang
Abstract : The Fe 3+ -doping in CeO2 :Fe/Yb/Er enhances upconversion luminescence by destroying the symmetry of the crystal field around Er 3+, which improves DSSC performance. Abstract : To make use of broad spectrum solar energy remains a main target in the photoelectrochemical area. Novel promising photoelectrode CeO2 :Fe/Yb/Er nanomaterials supported on upconversion nanomaterials doped with transition-metal ions are reported to improve broad spectrum absorption and scattering properties in dye-sensitized solar cells (DSSCs) for the first time. The results demonstrate that the materials have stronger upconversion luminescence than CeO2 :Yb/Er samples when the Fe 3+ ion doping concentration is 2 mol% and 33.5% higher photoelectric conversion efficiency than a pure P25 electrode, which are attributed to the special light scattering properties and excellent dye adsorption capacity of the CeO2 :Fe/Yb/Er nanomaterials. Accordingly, doping Fe 3+ transition metal ions in the upconversion material CeO2 :Yb/Er provides a new research idea for improving the photoelectric conversion efficiency of DSSCs.